How low can you go?: Understanding ecological footprint reduction in university students, faculty and staff. Issue 7 (6th November 2017) - Lambert, Matthew; Cushing, Katherine Kao
Abstract : Purpose: The purpose of this paper is to describe the impacts of an ecological footprint (EF) reduction campaign on the pro-environmental behavior of university students, faculty and staff. The campaign emphasized educating participants on specific actions that reduce resource use and the relative environmental benefit of each action. Design/methodology/approach: This investigation used a pre-test–post-test design. At the beginning of an academic year, participants were invited to measure their baseline EF and take part in a footprint reduction campaign. At the end of the campaign, participants measured their EF again to see if they were able to reduce it by 10 per cent. Findings: Participants in the footprint reduction campaign decreased their EF by 10 per cent. Students changed behaviors related to goods and services the most, resulting in a 16 per cent decrease in footprint for this behavior category. The most significant behavior change for faculty and staff was in the housing category with footprint reductions of 12 and 11 per cent, respectively. The most common behavioral changes in students were low- and no-cost options. Research limitations/implications: Because of the general nature of the EF tool, estimates of resource use reduction are approximate. Data describing pro-environmental behaviors were self-reported by participants, making accuracy dependent on participant recollections. Originality/value: This paper illustrates how providing quantitative, personalized and university-specific knowledge on the impact of personal lifestyles on natural resources can facilitate significant, measurable pro-environmental behavioral change for the entire campus community. It also provides direction on how to develop targeted sustainability campaigns for different audiences.